Analisis Yuridis Pertanggungjawaban Pidana terhadap Pelaku Penangkapan Ikan dengan Menggunakan Jaring Trawl Secara Illegal (Studi Putusan Nomor 1/Pid.Sus-PRK/2024/PN Mdn) - M. Syahrul; Rachmat Hidayat (Albayan Journal of Islam and Muslim Societies, 2024)
This research analyzes criminal liability for illegal fishing using trawl nets, based on Decision No. 1/Pid.Sus-PRK/2024/PN Mdn. The study employs a normative juridical method by examining statutory provisions and the judge’s reasoning in imposing sanctions. Findings show that the act of using trawl nets violates the Fisheries Law and environmental principles, as it damages marine ecosystems and threatens sustainable fish resources. The judgment upholds both retributive and preventive goals by punishing the perpetrator while promoting environmental deterrence. The study concludes that legal enforcement in fisheries requires consistency and integration between criminal sanctions and sustainable development policy.